Upgrading the Investment Policy Framework of Public Pension Funds - Vittas, Dimitri (World Bank, Washington, DC, 2012)
Public pension funds have the potential to benefit from low operating costs because they enjoy economies of scale and avoid large marketing costs. But this important advantage has in most countries been dissipated by poor investment performance. The latter has been attributed to a weak governance structure, lack of independence from government interference, and a low level of transparency and public accountability. Recent years have witnessed the creation of new public pension funds in several countries, and the modernization of existing ones in others, with special emphasis placed on upgrading their investment policy framework and strengthening their governance structure. This paper focuses on the experience of four new public pension funds that have been created in Norway, Canada, Ireland and New Zealand. The paper discusses the safeguards that have been introduced to ensure their independence and their insulation from political pressures. It also reviews their performance and their evolving investment strategies. All four funds started with the romantic idea of operating as 'managers of managers' and focusing on external passive management but their strategies have progressively evolved to embrace internal active management and significant investments in alternative asset classes. The paper draws lessons for other countries that wish to modernize their public pension funds.